Psychological preparedness of adolescents for disasters - Nurwahid, Ardika; Novikasari, Linawati; Setiawati, Setiawati (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Indonesia has diverse disaster potential based on its location and Lampung Regency, Lampung Province, recorded 31 disasters from January 1 to August 2023. The latest data for 2024 shows three tornadoes and 15 earthquakes. Adolescents are a vulnerable community when disasters occur. This situation must be anticipated by providing educational videos on tsunami mitigation. Purpose: To determine psychological preparedness of adolescents for disasters. Method: This research was quantitative, using a pre-experimental method with a one-group prctest-posttest approach. The population in this study was 81 adolescents aged 10-19 sampling. Data analysis used univariate and bivariate methods using dependent t-tests. Results: The average knowledge of adolescents about tsunamis before being given educational digital video learming media was 8.3. The average knowledge of adolescents mean of 13.23. The results of data analysis indicate an effect of digital video leaning media on tsunamis on adolescents knowledge, with a mean of 4.700 and a p-value of 0.000<0.05. Conclusion: There is an effect of digital video learning media on adolescents knowledge in can provide health education about the dangers of tsunamis, through educational videos or animated disaster response simulation videos. Keywords: Adolescents Knowledge; Digital Media Video; Psychological Preparedness; Tsunami.